Architecture, Technology and the Uncanny: Infiltrating Space in “The Veldt” and in “The Digital House Project” - Bussing López, Ilse Marie (2017)
The original term for the uncanny—das Unheimliche —is inevitably linked to the home. Uncanny is that which is both homey and unhomey, and this ambiguity is precisely what causes it to be disorienting and frightening. This article addresses the inherent link of the uncanny to the home by comparing a literary text, “The Veldt” (1950) by Ray Bradbury, to architectural texts, mainly “The Digital House Project” (1998) by Hariri and Hariri. Bradbury’s prophetic text, first published in 1950, presents an unnerving picture of domesticity, technology and modernity, a picture that is eerily recreated in these technological homes. In order to illustrate the mediation of the uncanny through architectural space, this study will address two issues which contribute to this sense of unease within the architectural and literary home: first, the dehumanization of humans and the consequent humanization of the house, and second, the worrisome recurrence and proliferation of data within these homes. I argue that architectural space has always mediated the uncanny, and that today, this mediation is strengthened by the overpowering presence of technology in the home.    El término original para el concepto de lo siniestro —das Unheimliche — está inevitablemente enlazado a la noción de hogar. Lo siniestro remite a la vez a lo hogareño y reconfortante como a lo antihogareño o lo desconcertante, y es precisamente esta ambigüedad la que genera desorientación y terror. Este artículo se enfoca en la conexión intrínseca entre lo siniestro y el hogar, al comparar un texto literario, “The Veldt” (1950) de Ray Bradbury, con textos arquitec tónicos, principalmente “The Digital House Project” (1998) por Hariri y Hariri. El texto profético de Bradbury, publicado en 1950, presenta una imagen desconcertante de la domesticidad, de la tecnología y de la modernidad, una imagen que es recreada en estas  casas tecnológicas. Con el fin de ilustrar la mediación de lo siniestro a través del espacio arquitectónico, este análisis se enfocará en dos aspectos que contribuyen a esta sensación de turbación dentro del hogar en el plano arquitectónico y literario: primero, la deshumanización de los individuos y la consecuente humanización de la casa, y segundo, la recurrencia preocupante y la proliferación de información dentro de estas casas. Insisto en que el espacio arquitectónico siempre ha mediado lo siniestro y que, actualmente, esta mediación se fortalece por la presencia abrumadora de la tecnología en el hogar.